Atypical lateralization in neurodevelopmental and psychiatric disorders: What is the role of stress?. (April 2020) - Berretz, Gesa; Wolf, Oliver T.; Güntürkün, Onur; Ocklenburg, Sebastian
Abstract: Hemispheric asymmetries are a major organizational principle of the human brain. In different neurodevelopmental and psychiatric disorders, like schizophrenia, autism spectrum disorders, depression, dyslexia and posttraumatic stress disorder, functional and/or structural hemispheric asymmetries are altered compared to healthy controls. The question, why these disorders all share the common characteristic of altered hemispheric asymmetries despite vastly different etiologies and symptoms remains one of the unsolved mysteries of laterality research. This review is aimed at reviewing potential reasons for why atypical lateralization is so common in many neurodevelopmental and psychiatric disorders. To this end, we review the evidence for overlaps in the genetic and non-genetic factors involved in the ontogenesis of different disorders and hemispheric asymmetries. While there is evidence for genetic overlap between different disorders, only few asymmetry-related loci have also been linked to disorders and importantly, those effects are mostly specific to single disorders. However, there is evidence for shared non-genetic influences between disorders and hemispheric asymmetries. Most neurodevelopmental and psychiatric disorders show alterations in the hypothalamic-pituitary adrenocortical (HPA) axis and maternal as well as early life stress have been implicated in their etiology. Stress has also been suggested to affect hemispheric asymmetries. We propose a model in which early life stress as well as chronic stress not only increases the risk for psychiatric and neurodevelopmental disorders but also changes structural and functional hemispheric asymmetries leading to the aberrant lateralization patterns seen in these disorders. Thus, pathology-related changes in hemispheric asymmetries are not a factor causing disorders, but rather a different phenotype that is affected by partly overlapping ontogenetic factors, primarily stress.